(3eNJUQ JGQjN OeTb dGHf YSGcQs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s; (3Ydj Hf GdMSf Hf gHI Gddg GdOeTbj , CHh GdbGSe, KbI GdOjf GHf YSGcQ,J (B600 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH GTJbGb ef GSe GdJGQjN s
(3GdhQbI GdChdi eXdeIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs